2022
DOI: 10.3390/ijerph191811714
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Experience of the COVID-19 Pandemic among Italian University Students: A Mixed-Method Study

Abstract: A vast amount of literature has highlighted that restrictions imposed by the COVID-19 pandemic, such as lockdowns and the resulting interruption of face-to-face academic activities, strongly disrupted students’ daily routine and undermined their well-being. Through a mixed method approach, this study was aimed at investigating the association between students’ experience of the health emergency and their resilience levels during the first pandemic outbreak. Between April and May 2020, 421 Italian university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…As some studies among university students have shown, the conditions experienced during the pandemic have affected health in general. Specifically, to a greater extent, mental health affects the capacity for resilience, as studies carried out in Portugal [33] and other countries have shown [34][35][36]. On the other hand, with respect to sex differences, the male students in our study had statistically significant average scores higher than the women, coinciding with a study carried out among young Spanish university students [3] and with other research that analyzes the influence of sex on resilience among young people [37].…”
Section: Discussionsupporting
confidence: 85%
“…As some studies among university students have shown, the conditions experienced during the pandemic have affected health in general. Specifically, to a greater extent, mental health affects the capacity for resilience, as studies carried out in Portugal [33] and other countries have shown [34][35][36]. On the other hand, with respect to sex differences, the male students in our study had statistically significant average scores higher than the women, coinciding with a study carried out among young Spanish university students [3] and with other research that analyzes the influence of sex on resilience among young people [37].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, other studies confirm that COVID-19 and its associated disruptions resulted in a substantial increase in stress, anxiety, depression, and suicidality among university students. In families where either a high school or a college student experienced educational disruption due to COVID-19, other family members reported increased stress as a result of that disruption [ 44 , 45 , 46 , 47 ].…”
Section: Literature Review: Covid-19 and The Mental Health And Psycho...mentioning
confidence: 99%
“…In this descriptive and explanatory mixed-method study, we collected both quantitative and qualitative data to provide an integrated view of how the COVID-19 pandemic impacted people's psychophysical well-being (McAdams et al, 2001;Anguera et al, 2020;Cipolletta et al, 2022;Mourad et al, 2022). We collected and analyzed self-report validated questionnaires measuring psychological well-being, as well as qualitative data through an open-ended question about the lived experience during the first lockdown period.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…During the last couple of years, many studies probed the experience of the first wave of the pandemic through a mixed-method design, collecting both qualitative and quantitative data. Among those studies, those which combined validated questionnaires and open-ended questions or in-depth interviews focused on specific populations, mainly health care workers, nurses and doctors (e.g., Svantesson et al, 2022;Harris et al, 2023;Richards et al, 2023), but also medical students (Rolland, 2022), family caregivers (Leleszi-Tróbert et al, 2022), women with young children (Wandschneider et al, 2022), children with obesity (Welling et al, 2022), supermarket workers (Mayer et al, 2022), and university students (Mourad et al, 2022). To our knowledge, three studies explored the effects of stress during the first wave of the pandemic through a mixed-method design.…”
Section: Introductionmentioning
confidence: 99%